2017
DOI: 10.1590/0001-3765201720160446
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous enzyme complex prevents intestinal soybean meal-induced enteritis in Mugil liza (Valenciennes, 1836) juvenile.

Abstract: Four soybean meal-based diets containing increasing levels of an enzyme complex (E50, E100, E150 and E200 at 50, 100, 150 and 200 g ton -1 , respectively) and one soybean meal-based diet without the enzyme complex (E0) were fed in triplicate to M. liza juveniles in a semi-static flow system with 20 fish per tank for 75 days. There were no differences between the treatments for animal performance parameters, but fish fed the enzyme complex treatment exhibited significantly (P<0.05) higher values of calcium bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Several effective methods were conducted to overcome the antinutritional effect of SBM in aquaculture, including deceasing its content in diets (Bonvini et al, ), or supplementation with methionine and phosphate (Kokou et al, ), phosphorus and magnesium (Imanpoor & Bagheri, ), glutamine and arginine (Gu et al, ), lysine and methionine (Jiang et al, ), hydrolysed feather meal (Zhang et al, ), exogenous enzyme complex (Ramos et al, ), mannan oligosaccharides (MOS) (Torrecillas et al, ) or lactoferrin (Ulloa et al, ) in diets with SBM. Scientists were also looking for other plant protein sources, such as cottonseed meal (CSM) (Lee, Dabrowski, Blom, Bai, & Stromberg, ), chickpeas meal (CPM) (Christodoulou et al, ), extruded canola seed‐pea (ECSP) (Bandegan et al, ), rubber seed meal (RSM) (Deng, Mai, Chen, Mi, & Zhang, ) or fermented Jatropha kernel meal (FJKM) (Phulia et al, ) to partially or totally replace SBM in aquafeeds.…”
Section: Introductionmentioning
confidence: 99%
“…Several effective methods were conducted to overcome the antinutritional effect of SBM in aquaculture, including deceasing its content in diets (Bonvini et al, ), or supplementation with methionine and phosphate (Kokou et al, ), phosphorus and magnesium (Imanpoor & Bagheri, ), glutamine and arginine (Gu et al, ), lysine and methionine (Jiang et al, ), hydrolysed feather meal (Zhang et al, ), exogenous enzyme complex (Ramos et al, ), mannan oligosaccharides (MOS) (Torrecillas et al, ) or lactoferrin (Ulloa et al, ) in diets with SBM. Scientists were also looking for other plant protein sources, such as cottonseed meal (CSM) (Lee, Dabrowski, Blom, Bai, & Stromberg, ), chickpeas meal (CPM) (Christodoulou et al, ), extruded canola seed‐pea (ECSP) (Bandegan et al, ), rubber seed meal (RSM) (Deng, Mai, Chen, Mi, & Zhang, ) or fermented Jatropha kernel meal (FJKM) (Phulia et al, ) to partially or totally replace SBM in aquafeeds.…”
Section: Introductionmentioning
confidence: 99%
“…Moita et al [72] reported that phytase supplementation increased VH in birds, and this parameter has been correlated with greater nutrient absorption and utilization owing to the fact that longer villi may be an indicator of increased absorptive capacity and the existence of mature enterocytes [73,74]. In the same sense, Ramos et al [75] described that exogenous phytase supplementation (up to 1,696 FTU/kg) even at a low level (814 FTU/kg) reduced the intestinal damage caused by a soybean meal-based diet in Mugil liza juveniles. However, Ranjan et al [76] found no changes in the intestinal structure in Labeo rohita fed diets supplemented with 500 FTU/kg.…”
Section: Discussionmentioning
confidence: 95%
“…This may be due to the direct effect of the added enzymes or to the indirect effect by stimulating the secretion of self-enzymes in fishes or by increasing the number of beneficial bacteria in the gastrointestinal tract (Ng & Chen, 2002;Lin et al, 2007). Ramos et al (2017) found that adding enzymes break down polysaccharides, such as hemicellulase, pectin and phytates in soybeans, caused increased food viscosity and slow gastric emptying. Castillo & Gatlin III (2015) also noted an improvement in secretion and increased activity of trypsin, chymotrypsin, lipase and amylase enzymes, as well as an increase in the number of Lactobacillus bacteria.…”
Section: Discussionmentioning
confidence: 99%